Robocop - The depersonalisation of police officers and their emotions: a diary study of emotional labor and burnout in front line British police officers - Lennie, Sarah-Jane (International journal of law, crime and justice, 2020)
Policing has long been recognized as an emotionally distressing and stressful occupation, and recent years have seen a marked increase in psychological illness within the police service of Britain. Research into the emotional labor of police officers and its psychological consequences is limited and has predominately engaged quantitative methodologies. This paper takes a mixed methods approach, exploring emotional labor and the relationship with burnout within a large police force in the north of England. The use of audio diary provides in-depth exploration of feeling and display rules operating within the police service. Narrative analysis of thirty-eight audio diary entries and a focus group is integrated with results from the Maslach and Jackson Burnout Inventory. Findings indicated depersonalisation as a requirement of feeling and display rules, a strategy also used as a form of coping, as well as experienced as an aspect of burnout. Emotional suppression went beyond interactions with members of the public, continuing into peer and family relationships, with many officers never expressing their true emotions. This presents an important opportunity for the police service of England and Wales to better understand and respond to the emotional pressures and coping mechanisms that officer's experience within their lives.